Effect of the matrix material and electroplating process on the microstructure and properties of isolation switch contacts. (30th October 2020) - Qianqian, Yang; Zhang, Changle; Yuan, Liu; Molin, Zhao; Yao, Wang; Xinghai, Shao; Shouhong, Xue; Biao, Wang; Yu, Xu; Yutong, Lv
Abstract: In the KI system, Ag plating, hard-Ag plating and graphene-Ag plating were prepared on the surface of the copper and Cu–Cr alloy matrix materials by the electrodeposition method. The purpose of this paper is to define the copper-based material and related plating process suitable for the contacts of the isolating switch, obtaining excellent comprehensive properties and revealing the strengthening mechanism and wear mechanism of contact materials. Copper alloy was obtained by smelting in a high-frequency vacuum induction furnace, and then cold rolled. Effects of different plating processes and matrix materials on the microstructure, bonding degree between the plating and matrix, microhardness, contact resistance and wear resistance of copper-based contact materials were studied. The results showed that the matrix and the plating are well bonded. Both the Cu–Cr alloy matrix and the hard-Ag plating were rich in a large number of nano twins, dislocations and precipitates, which can strengthen the matrix and the plating. Moreover, they are beneficial to obtaining contact materials with high strength, high toughness and high conductivity. The contact resistance of the 3 kinds of plating changed little. The contact resistance of the Ag plating was the smallest, which was the largest of the hard-Ag plating, increased by 19.5%. The hard-Ag plating has the highest hardness and best wear resistance. Under the same test conditions, the combination of the hard-Ag plating and the Cu–Cr alloy matrix enables the copper-based contact material to obtain good cooperation of hardness, wear resistance and conductivity, and the comprehensive performance is the best.